A Portrait of Remedial Instruction: Faculty Workload and Assessment Techniques - Boyer, Patricia Grace; Butner, Bonita K.; Smith, Dwyane (Higher Education, 2007)
Remediation in postsecondary education continues to be an issue that is hotly debated by institutional leaders and state policymakers. The National Center for Education Statistics [The National Center for Education Statistics. (2003). Remedial education at higher education institutions in fall 2000. PEQIS. Washington, D.C.: U.S. Department of Education.] estimates that 98% of public 2-year and 80% of public 4-year institutions offered at least one remedial course. The need for remedial courses is also demonstrated by the growing number of students who enroll each year. Studies that examine students and placement are found in the literature, but few examine the faculty who teach in remedial programs [Boylan, H., Bonham, B. S., Jackson, J., & Saxon, D. P. (1995). Research in Developmental Education, 12(1), 42–52.]. The purpose of this study was to examine faculty who teach remedial courses. In particular, we were interested in faculty workload and the assessment techniques employed by faculty based upon type and level of institution. More specifically, data was analyzed using the NSOPF: 99 database on faculty at 2-year and 4-year institutions as well as faculty at private and public institutions. Some comparisons between faculty teaching remedial courses and nonremedial courses are presented.
7 citations (Crossref) [2023-10-31]
Keywords: Assessment techniques; Faculty workload; Institutional type; NSOPF: 99; Remediation; dept.pres; peer-reviewed